Hubungan Antara Kohesivitas Dan Motivasi Berprestasi Dengan Kemalasan Sosial (Social Loafing) Pada Mahasiswa Jurusan Psikologi Universitas Negeri Padang - Elvia Wulan Heksa Paksi; Ria Okfrima; Rina Mariana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this research was to determine (1) ) the relationship between cohesiveness with social loafing on psychology students class 2017 & 2018 Padang state University, (2)The relationship between achievement motivation and social loafing on psychology students class 2017 & 2018 Padang State University, (3) The relationship between cohesiveness and achievement motivation with social loafing on psychology students class 2017 & 2018 Padang State University. The instrument of this research are social loafing scale with validity coefficient from 0,326 up to 0,623 and reliability of 0,876, cohesiveness scale with coefficient validity from 0,313 up to 0,714 and reliability of 0,773 and achievement motivation scale with coefficient validity from 0,313 up to 0,714 and reliability of 0,893. Data analysis of this research using multiple corelation . The result showed that there was a relationship between cohesiveness and achievement motivation with social loafing on psychology students class 2017 & 2018 Padang State University, with Fstatistic>Ftable(23,965 > 7,71), p-value = 0,000 (p-value < 0,01), r value = 0,287 , and R square value = 0,287 or 28,7%. Partially, there was a negative and significant relationship between cohesiveness and social loafing, with rxy= -0,532 (p-value 0,000<0,01). The effective contribution of self cohesiveness towards social loafing was 28%, while the contribution of achievement motivation with social loafing was 10%.